An Isotope‐Coded Fluorogenic Cross‐Linker for High‐Performance Target Identification Based on Photoaffinity Labeling1. (7th November 2014) - Tomohiro, Takenori; Morimoto, Shota; Shima, Toshiya; Chiba, Junya; Hatanaka, Yasumaru
Abstract A photoaffinity labeling (PAL)‐based method for the rapid identification of target proteins is presented in which a high‐performance chemical tag, an isotope‐coded fluorescent tag (IsoFT), can be attached to the interacting site by irradiation. Labeled peptides can be easily distinguished among numerous proteolytic digests by sequential detection with highly sensitive fluorescence spectroscopy and mass spectrometry. Subsequent MS/MS analysis provides amino acid sequence information with a higher depth of coverage. The combination of PAL and heterogeneous target‐selecting techniques significantly reduces the amount of time and protein required for identification. An additional photocleavable moiety successfully accelerated proteomic analysis using cell lysate. This method is a widely applicable approach for the rapid and accurate identification of interacting proteins.